The evolving role of weather types on rainfall chemistry under large reductions in pollutant emissions. (15th April 2022) - Tso, Chak-Hau Michael; Monteith, Don; Scott, Tony; Watson, Helen; Dodd, Beverley; Pereira, M. Glória; Henrys, Peter; Hollaway, Michael; Rennie, Susannah; Lowther, Aaron; Watkins, John; Killick, Rebecca; et al.
Abstract: Long-term change and shorter-term variability in the atmospheric deposition of pollutants and marine salts can have major effects on the biogeochemistry and ecology of soils and surface water ecosystems. In the 1980s, at the time of peak acid deposition in the UK, deposition loads were highly dependent on prevailing weather types, and it was postulated that future pollution recovery trajectories would be partly dependent on any climate change-driven shifts in weather systems. Following three decades of substantial acidic emission reductions, we used monitoring data collected between 1992 and 2015 from four UK Environmental Change Network (ECN) sites in contrasting parts of Great Britain to examine the trends in precipitation chemistry in relation to prevailing weather conditions. Weather systems were classified on the basis of Lamb weather type (LWT) groupings, while emissions inventories and clustering of air mass trajectories were used to interpret the observed patterns. Concentrations of ions showed clear differences between cyclonic-westerly-dominated periods and others, reflecting higher marine and lower anthropogenic contributions in Atlantic air masses. Westerlies were associated with higher rainfall, higher sea salt concentrations, and lower pollutant concentrations at all sites, while air mass paths exerted additional controls. Westerlies therefore have continued to favour higher sea salt fluxes, whereas emission reductions are increasingly leading to positive correlations between westerlies and pollutant fluxes. Our results also suggest a shift from the influence of anthropogenic emissions to natural emissions (e.g., sea salt) and climate forcing as they are transported under relatively cleaner conditions to the UK. Westerlies have been relatively frequent over the ECN monitoring period, but longer-term cyclicity in these weather types suggests that current contributions to precipitation may not be sustained over coming years. Graphical abstract: Image 1 Highlights: Atmospheric circulation types continue to exert a strong control on UK rainfall composition. Seasalt deposition and rainfall increases with the number of westerlies. Pollutant concentrations decreases with the number of westerlies. Convective rainfall effects are less clear due to sampling limitations. Effects on soil organic carbon due to long-term variation of westerlies frequency is postulated.